LCA of a Mass Housing Area from an Energy Based Economy Perspective - Mert, Yelda; Mert, Suha Orcun (International Journal of Contemporary Economics and Administrative Sciences, 2018)
As a technique that covers a system or environment from cradle-to-grave, Life-Cycle Assessment (LCA) assesses an environment-economy associated evaluation considering all the stages of a product's life. Buildings and settlement zones are known to be major energy consumption areas that lead to emission of significant amounts of greenhouse gases and to economic losses. In this study, the efficiency analysis of the YYÜ TOKİ Lodgments is conducted through the energy based economic LCA analysis. A comprehensive energy analysis is made to evaluate the economic LCA of the energy system in this settlement area, utilizing year-long temperature measurements for outside and indoors. The results of the study indicate a large potential of economic benefit conservation for the case area despite the fact that energy performances of sample site are relatively high compared to the current building stock averages of Turkey.